ИНСАНДА КӨРКЕМ-ДӨРЕТИЎШИЛИК УҚЫПЛЫЛЫҚЛАРЫН РАЎАЖЛАНДЫРЫЎДЫҢ ТИЙКАРҒЫ АСПЕКТЛЕРИ - Уразимова, Т.В. (FAN va JAMIYAT, 2021)
The article is devoted to the aspects of artistic and creative development of the individual in modern society. This problem of science is one of the most pressing issues of today.